Expectations of Customers Regarding Service Quality at Convention Hotels: A Case Study of Phuket, Thailand - Soonsan, Nimit (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The study of the expectation of customers regarding service quality at convention hotels: a case study of Phuket, Thailand aimed to study: 1) the demographic characteristics of the customers’ expectations of service quality at the convention hotels in Phuket, and 2) the expectation factors affecting the characteristics of service quality at the convention hotels in Phuket. This quantitative research was conducted by gathering data from the sample group of 384 customers using the convention hotels in Phuket. The questionnaires were used as the instrument of the study. The data was analyzed by using descriptive statistics, for example frequency, percentage, mean, and standard deviation. The variables relationships were also tested by using Chi-square and T-test. The findings were as follows: 1) age, status, and the highest level of education affected the expectation factors of service quality of the convention hotels in Phuket, 2) the factor that affected customers’ expectations of service quality in the convention hotels in Phuket is past experiences of service. Another factor is the word of mouth communication from others. In addition, the factor that has no effect on the level of service quality expectation is personal needs. The recommendation of the study is to increase the efficient service strategy in order to meet customers’ needs. The recommendations about the service quality of venues in Phuket are to be reliable, to focus on the tangible, to perform with assurance, to increase the efficiency of the responsiveness and to be empathetic.